Vulnerability to physical inactivity: evidence of content validity and response processes - Déborah Santana Pereira; Raquel Sampaio Florêncio; Virna Ribeiro Feitosa Cestari; Thereza Maria Magalhães Moreira (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To analyze content validity evidence and response processes of a bank of items for measuring vulnerability to physical inactivity in adults. Method: Methodological study, with 13 specialists and 46 representatives of the target population. The Content Validity Index (CVI) and binomial test were calculated; data obtained through validity based on response processes were collected through interviews. Results: Of the 105 constructed items, 16 were excluded (CVI<0.78); 89 items showed agreement <80% in the psychometric criteria, being modified. Of the 101 items that remained (CVI>0.78), 34 were changed and 4 were deleted after evaluating the evidence of response processes. In the end, 97 items remained, with a global CVI of 0.92, organized into two dimensions: Subject (CVI=0.91) and Social (CVI=0.94). Conclusion: The items presented adequate parameters and evidence of validity; and can subsidize the construction of instruments that consider the subject's and social vulnerability in understanding physical inactivity.